Effect of ultra‐high molecular weight polyethylene fiber on the early mechanical strength and shrinkage crack resistance of concrete. (8th December 2021) - Chen, Zhiyou; Yu, Lin; Jin, Weizhun; Jiang, Linhua; Guo, Mingzhi
Abstract: This study investigates the early mechanical strength, and shrinkage crack resistance of ultra‐high molecular weight polyethylene (UHMWPE) fiber concrete with different lengths and contents. The microstructure of UHMWPE fiber concrete is investigated by scanning electronic microscope (SEM) to analyze the distribution and mechanism of action of UHMWPE fiber in concrete. The mechanical strength results indicate that the compressive strength and splitting tensile strength of concrete increase first and then decrease by adding fibers. The maximum compressive strength and splitting tensile strength at age of 28d are 42.9 and 3.32 MPa, which is 41.1% and 55.9% higher than that of the benchmark group. The SEM results show that when the UHMWPE fiber content is small, the fibers are evenly distributed in concrete and tightly bonded to the matrix. While the fibers will agglomerate and entangle with the increase of the fiber content, the results of shrinkage resistance test demonstrate that the 12 mm fiber with 0.24% fiber volume content can obtain the best shrinkage crack resistance.